Immune response to 2009 H1N1 vaccine in HIV-infected adults in Northern Thailand - Nuntisa Chotirosniramit (2018)
Background: In late 2009, the Thai Ministry of Public Health provided two million doses of the monovalent pandemic influenza H1N1 2009 vaccine (Panenza® Sanofi Pasteur), which was the only vaccine formulation available in Thailand, to persons at risk of more severe manifestations of the disease including HIV infection. Several studies have shown poorer immune responses to the 2009 H1N1 vaccines in HIV-infected individuals. There are limited data in this population in resource-limited countries. Results: At day 28 post-vaccination, seroconversion was found in 32.0% (95% CI 24.5-40.2) of the HIV-infected group and 35.0% (95% CI 15.4-59.2) of the healthy controls (p = 0.79). Seroprotection rate was observed in 33.3% (95% CI 25.8-41.6) and 35.0% (95% CI 15.4-59.2) of the HIV-infected group and the control group, respectively (p = 0.88). Among HIV-infected participants, the strongest factor associated with vaccine response was age 42 y or younger (p = 0.05). Methods: We evaluated the immunogenicity of a single, 15μg/0.5ml dose of a monovalent, non-adjuvanted 2009 H1N1 vaccine in 150 HIV-infected Thai adults and 20 healthy controls. Immunogenicity was measured by hemagglutination inhibition assay (HI) at baseline and 28 d after vaccination. Seroconversion was defined as 1) pre-vaccination HI titer < 1:10 and post-vaccination HI titer ≥ 1:40, or 2) pre-vaccination HI titer ≥ 1:10 and a minimum of 4-fold rise in post-vaccination HI titer. Seroprotection was defined as a post-vaccination HI titer of ≥ 1:40. Conclusions: A low seroconversion rate to the 2009 H1N1 vaccine in both study groups, corresponding with data from trials in the region, may suggest that the vaccine used in our study is not very immunogenic. Further studies on different vaccines, dosing, adjuvants, or schedule strategies may be needed to achieve effective immunization in HIV-infected population. © 2012 Landes Bioscience.